Critical Success Factors of New Product Development and Impact on Performance of Malaysian Automotive Industry - Fazilah, Abdul Aziz; Nur Najmiah, Jaafar; Suraya, Sulaiman (Trans Tech Publications, Switzerland, 2014)

(untitled)
This research paper shows a framework to conduct an empirical study in Malaysian automotive industry in order to improve their performance. There are factors which are effective factors in improving performance of Malaysian automotive companies namely top management support, cross functional teamwork, new product development (NPD) process, NPD strategies, and market research activities. The critical success factor of NPD is playing a fundamental role in determining the performance in Malaysian automotive companies. In this research study, a framework has been developed that includes critical success factors of NPD and project achievement to study their influence on the performance of Malaysian automotive companies. It is hoped that this paper can provide an academic source for both academicians and managers due to investigate the relationship between critical success factors of total NPD, project achievement and company performance in a systematic manner to increase successful rate of NPD progress.